The Law in the Face of the COVID-19 Pandemic: Early Lessons from Uruguay - Norouzi, Nima; Khanmohammadi, Heshmat-ullah; Ataei, Elham (Faculty of Law, Hasanuddin University, 2021)
The Corona crisis is one of the crises that has engulfed the world and Uruguay and has marked all human beings' death and life. This crisis has many legal, political, social, and economic dimensions and has and will have different consequences in this area. So far in the last two centuries, twelve major epidemics of infectious diseases and fifteen famines, and severe droughts have engulfed our world, but this crisis is